Impact of Technology Education and Digital Skill Mastery on Millennial Generation Readinesss: Labor Market Revolution on Automation and Artificial Intelligence Era - Sri Hardani Marbun; Sujoko Sujoko (PT. Hafasy Dwi Nawasena, 2025)
This study is motivated by the changes in the labor market due to the Fourth Industrial Revolution, which requires technology and digital skills for millennials in Yogyakarta. In facing the challenges of automation and artificial intelligence, this generation needs to master these skills to be ready to compete in the workforce. The study uses a quantitative approach with a descriptive-correlational design, involving 385 respondents selected using purposive sampling. Data were collected through an online questionnaire distributed via social media. Data analysis was conducted using SPSS software, with hypothesis testing using t-tests and F-tests. The results show that both technology-based education and digital skills have a positive and significant impact on the readiness of millennials to face changes in the labor market. The combination of these two factors also significantly contributes to their readiness. These findings are expected to provide a foundation for the development of more effective educational and training policies to prepare millennials to face the challenges of the automation and artificial intelligence era.